Hepatic arterial infusion pump chemotherapy combined with systemic therapy for patients with advanced colorectal liver metastases: Outcomes in a newly established program. Issue 3 (6th May 2022) - Walker, Brett S.; Billingsley, Kevin G.; Sutton, Thomas L.; Kolbeck, Kenneth J.; Korngold, Elena K.; Nabavizadeh, Nima; Dewey, Elizabeth N.; Herzig, Daniel O.; Lopez, Charles D.; Mayo, Skye C.
Abstract: Background and Objectives: Colorectal liver metastasis (CRLM) is a leading cause of morbidity and mortality in patients with colorectal cancer. Hepatic arterial infusion (HAI) chemotherapy has been demonstrated to improve survival in patients with resected CRLM and to facilitate conversion of technically unresectable disease. Methods: Between 2016 and 2018, n  = 22 HAI pumps were placed for CRLM. All patients received systemic chemotherapy concurrently with HAI floxuridine/dexamethasone. Overall survival (OS) and progression‐free survival (PFS) were assessed using the Kaplan–Meier method. Results: HAI pumps were placed in seven patients with completely resected CRLM and 15 patients with unresectable disease. Twenty‐one patients received HAI floxuridine with a median of 5 total HAI cycles (interquartile range: 4–7). Biliary sclerosis was the most common HAI‐related complication ( n  = 5, 24%). Of the 13 patients treated to convert unresectable CRLM, 3 (23%) underwent hepatic resection with curative intent after a median of 7 HAI cycles (range: 4–10). For all HAI patients, the mean OS was 26.7 months from CRLM diagnosis, while the median PFS and hepatic PFS from pump placement were 9 and 13 months, respectively. Conclusion: Concomitant HAI and systemic therapy can be utilized at multidisciplinary programs for patients with advanced CRLM, both in the adjuvant setting and to facilitate conversion of unresectable disease.